Discharge by frustration / Haliza Anis Abu Amin - Abu Amin, Haliza Anis (Faculty of Law, 1987)
A contract is an agreement that is legally binding between the parties. Under it both parties are bound to perform their respective obligation. But when a contract is said to be discharged, the contracting parties are free from performing further obligation arising from it. A contract may be discharged by one of the following ways: 1. by performance 2. by breach 3. by consent or agreement between the parties 4. by frustration For the purpose of this project, an attempt will be made to consider the discharge of contract by frustration. A contract is frustrated when subsequent to the formation that there is a change in the circumstances which causes a contract to be legally or physically impossible to be performed.